2004
DOI: 10.1074/jbc.m410378200
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of β-Site β-Amyloid Precursor Protein-cleaving Enzyme

Abstract: Cleavage of the ␤-amyloid precursor protein (APP) by the aspartyl protease ␤-site APP-cleaving enzyme (BACE) is the first step in the generation of the amyloid ␤-peptide, which is deposited in the brain of Alzheimer's disease patients. Whereas the subsequent cleavage by ␥-secretase was shown to originate from the cooperation of a multicomponent complex, it is currently unknown whether in a cellular environment BACE is enzymatically active as a monomer or in concert with other proteins. Using blue native gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 67 publications
(75 reference statements)
5
98
1
Order By: Relevance
“…6) (our unpublished observations). Furthermore, it has been reported that full-length BACE1, forming a high-molecular-weight complex associated with lipid, exhibits higher enzymatic activity than that of C-terminally truncated BACE1 (1-454) (Marlow et al, 2003;Westmeyer et al, 2004). This may support the view that lipophilic TAK-070 effectively reaches the membrane-associated BACE1 complex.…”
Section: Discussionsupporting
confidence: 74%
“…6) (our unpublished observations). Furthermore, it has been reported that full-length BACE1, forming a high-molecular-weight complex associated with lipid, exhibits higher enzymatic activity than that of C-terminally truncated BACE1 (1-454) (Marlow et al, 2003;Westmeyer et al, 2004). This may support the view that lipophilic TAK-070 effectively reaches the membrane-associated BACE1 complex.…”
Section: Discussionsupporting
confidence: 74%
“…BACE1 was cotransfected with either control vector or TMEM59 into HEK293 cells. In control cells BACE1 was mainly present in a mature and to a low extent in an immature form, in agreement with previous publications (58,59). The mature form is complex N-glycosylated and resistant to treatment with endoglycosidase H, which only removes N-linked sugars that are not complex glycosylated (Fig.…”
Section: Tmem59supporting
confidence: 79%
“…These include: heparan sulphate proteoglycans [45,46], cholesterol [47,48] lipid rafts [36,37,49], reticulon family members [50,51] and PAR-4 [52]. Changed V max in the presence of unchanged K m may reflect the loss of a non-competitive inhibitor of b-secretase activity in AD brain, and increased V max for b-secretase has been observed with BACE1 dimerisation [53].…”
Section: Discussionmentioning
confidence: 99%